2021
DOI: 10.1186/s40814-021-00809-z
|View full text |Cite|
|
Sign up to set email alerts
|

Very preterm infants engage in an intervention to train their control of attention: results from the feasibility study of the Attention Control Training (ACT) randomised trial

Abstract: Background Very premature birth (gestational age between 28 and 31 + 6 weeks) is associated with increased risk of cognitive delay and attention deficit disorder, which have been linked to anomalies in the development of executive functions (EFs) and their precursors. In particular, very preterm (VP) infants display anomalies in controlling attention and gathering task-relevant information. Early interventions that support attention control may be pivotal in providing a secure base for VP child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…Sample sizes were relatively small in the majority of the studies: only five studies included more than fifty subjects [ 25 , 36 , 39 , 46 , 48 ]; ten had 25–50 subjects [ 28 , 29 , 32 , 34 , 37 , 41 , 43 , 44 , 45 , 47 ]; and seven had 10–25 subjects [ 30 , 31 , 33 , 35 , 38 , 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes were relatively small in the majority of the studies: only five studies included more than fifty subjects [ 25 , 36 , 39 , 46 , 48 ]; ten had 25–50 subjects [ 28 , 29 , 32 , 34 , 37 , 41 , 43 , 44 , 45 , 47 ]; and seven had 10–25 subjects [ 30 , 31 , 33 , 35 , 38 , 40 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the calculator showed specificity for ADHD compared to other common child psychopathology (anxiety disorders and oppositional defiant disorder). Although an emerging literature is suggesting that early interventions might have a role for individuals at risk for ADHD (Perra et al., 2021), the choice of a clinically reasonable range of appropriate risk thresholds will depend on (a) further validity studies, (b) characteristics of future early interventions, and (c) individual clinician and parental preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions are being developed specifically for the prevention of ADHD in VP/VLBW infants. A recent study (Perra et al., 2021) shows the feasibility of delivering a cognitive training program to infants about 1 year of age born VP. They were able to engage adequately in a cognitive training intervention to train their control of attention, improving performance across training visits, and achieving good treatment adherence and acceptability of outcome measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors reported an omission in the list of authors, having failed to recognise Aaron Patterson for his contribution to data collection.…”
mentioning
confidence: 99%